Pengaruh Harga Crude Oil Dan Additive (Over Head Base Oil) Terhadap Penentuan Harga Base Oil Di Pasar Serta Implikasinya Terhadap Profitabilitas Perusahaan-Perusahaan Manufaktur Terkait Yang Terdaftar Di Bei - Aris Hidalatullah; Muhammad Yusuf; Wiwi Warsiati; Aggi Panigoro (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
Chandra Asri and PT. Gajah Tunggal Tbk. are the research objects which need base oil as their raw material. From the analysis, ROA of PT. Chandra Asri increased the average 117.89%, and ROA of PT. Gajah Tunggal Tbk. decrease as the average 41.7%. Allegedly changes in ROA are influenced by changes in the price of crude oil, additive, and base oil prices. The average price of crude oil has been decreased by 3.94%. The average increase of the additive price of the materials per semester was 0.45%. The average price of base oil has been decreased by 3.86%. The effect of crude oil price and additive price on base oil price and its implication on ROA is examined through correlation model, regression, hypothesis test and path analysis yielding the following findings; First; 94.9% base oil price (Y) is determined by the price of crude oil (X1). Predicted if X1 is changed one unit, then the value of Y is changed 0,032. From t test obtained significant influence between two variables. Second; 44.6% base oil price is determined by the price of Additive goods. Predicted when X2 is converted one unit, Y value is 1.029. From t test obtained significant influence between two variables. Third; 95.90% base oil price is determined by the price of Crude oil (X1) and the price of Additive (X2). Predicted when X1 and X2 are converted simultaneously by one unit then the value of Y is changing 0,030 and 0,188. From F test, there is no significant influence between X1 and X2 on Y. Fourth; 20.90% ROA (Z) is determined by the price of Crude oil (X1). Predicted when X1 is converted one unit, Z value down 8.253E-6. Test t proves there is no significant influence between the two variables. Fifth; 13.60% ROA (Z) is determined by the price of Additive Goods (X2). Predicted when X2 is changed one unit, Z value down 0.000311. t test proves there is no significant influence between the two variables. Sixth; 26.90% ROA (Z) is determined by the price of Base oil (Y). Predicted when Y is converted one unit, Z value down 0.000284. t test proves there is significant influence between both variables. Seventh; 22.20% ROA (Z) is determined by the price of Crude oil (X1) and Additive Goods (X2). Predicted if X1, and X2 change simultaneously one unit, the value of Z decreased by the coefficient of regression direction. F test proves there is no significant influence between X1 and X2 on ROA. Eighth; the price of Crude Oil (X1) directly affects Price Base oil (Y), the indirect influence of X1 through Y on Z is not significant. The price of additive goods (X2) directly affects the base oil price (Y). While the indirect effect of X2 through Y against Z is not significant. Predicted when X1 and X2 changed one unit of influence respectively 1.7779E-5 and 3.334E-5. Whereas if Y changes, Z goes down 0.001.Chandra Asri and PT. Gajah Tunggal Tbk. are the research objects which need base oil as their raw material. From the analysis, ROA of PT. Chandra Asri increased the average 117.89%, and ROA of PT. Gajah Tunggal Tbk. decrease as the average 41.7%. Allegedly changes in ROA are influenced by changes in the price of crude oil, additive, and base oil prices. The average price of crude oil has been decreased by 3.94%. The average increase of the additive price of the materials per semester was 0.45%. The average price of base oil has been decreased by 3.86%. The effect of crude oil price and additive price on base oil price and its implication on ROA is examined through correlation model, regression, hypothesis test and path analysis yielding the following findings; First; 94.9% base oil price (Y) is determined by the price of crude oil (X1). Predicted if X1 is changed one unit, then the value of Y is changed 0,032. From t test obtained significant influence between two variables. Second; 44.6% base oil price is determined by the price of Additive goods. Predicted when X2 is converted one unit, Y value is 1.029. From t test obtained significant influence between two variables. Third; 95.90% base oil price is determined by the price of Crude oil (X1) and the price of Additive (X2). Predicted when X1 and X2 are converted simultaneously by one unit then the value of Y is changing 0,030 and 0,188. From F test, there is no significant influence between X1 and X2 on Y. Fourth; 20.90% ROA (Z) is determined by the price of Crude oil (X1). Predicted when X1 is converted one unit, Z value down 8.253E-6. Test t proves there is no significant influence between the two variables. Fifth; 13.60% ROA (Z) is determined by the price of Additive Goods (X2). Predicted when X2 is changed one unit, Z value down 0.000311. t test proves there is no significant influence between the two variables. Sixth; 26.90% ROA (Z) is determined by the price of Base oil (Y). Predicted when Y is converted one unit, Z value down 0.000284. t test proves there is significant influence between both variables. Seventh; 22.20% ROA (Z) is determined by the price of Crude oil (X1) and Additive Goods (X2). Predicted if X1, and X2 change simultaneously one unit, the value of Z decreased by the coefficient of regression direction. F test proves there is no significant influence between X1 and X2 on ROA. Eighth; the price of Crude Oil (X1) directly affects Price Base oil (Y), the indirect influence of X1 through Y on Z is not significant. The price of additive goods (X2) directly affects the base oil price (Y). While the indirect effect of X2 through Y against Z is not significant. Predicted when X1 and X2 changed one unit of influence respectively 1.7779E-5 and 3.334E-5. Whereas if Y changes, Z goes down 0.001.